2002
DOI: 10.1126/science.1074610
|View full text |Cite
|
Sign up to set email alerts
|

Air-Snow Interactions and Atmospheric Chemistry

Abstract: The presence of snow greatly perturbs the composition of near-surface polar air, and the higher concentrations of hydroxyl radicals (OH) observed result in a greater oxidative capacity of the lower atmosphere. Emissions of nitrogen oxides, nitrous acid, light aldehydes, acetone, and molecular halogens have also been detected. Photolysis of nitrate ions contained in the snow appears to play an important role in creating these perturbations. OH formed in the snowpack can oxidize organic matter and halide ions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
475
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 489 publications
(489 citation statements)
references
References 51 publications
11
475
0
3
Order By: Relevance
“…Snow is a material with a high surface area (1) that interacts with atmospheric chemistry through processes such as adsorption of trace gases, trapping of particles, and catalysis of heterogeneous photochemical reactions, resulting in a major impact on polar atmospheric chemistry (2). For example, measurements and models showed that falling snow adsorbs semivolatile organic chemicals (SVOCs) and removes them from the troposphere more efficiently than rain (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Snow is a material with a high surface area (1) that interacts with atmospheric chemistry through processes such as adsorption of trace gases, trapping of particles, and catalysis of heterogeneous photochemical reactions, resulting in a major impact on polar atmospheric chemistry (2). For example, measurements and models showed that falling snow adsorbs semivolatile organic chemicals (SVOCs) and removes them from the troposphere more efficiently than rain (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…As the NO 2 mixing ratios are low, a compensation point may cause plants within the ecosystem to release NO 2 , as observed on the leaf scale for tropical plants (Sparks et al, 2001). As the ground was covered by snow during the winter, a direct release of NO 2 as a result of snow photochemistry could also cause emission (Domine and Shepson, 2002). A third mechanism potentially responsible for the upward NO 2 fluxes is emission of NO, either from plants (Wildt et al, 1997) or snow (Domine and Shepson, 2002), followed by reaction with O 3 in the canopy, resulting in a net observed upward flux.…”
Section: Patterns In the Fluxesmentioning
confidence: 99%
“…As the ground was covered by snow during the winter, a direct release of NO 2 as a result of snow photochemistry could also cause emission (Domine and Shepson, 2002). A third mechanism potentially responsible for the upward NO 2 fluxes is emission of NO, either from plants (Wildt et al, 1997) or snow (Domine and Shepson, 2002), followed by reaction with O 3 in the canopy, resulting in a net observed upward flux. Fluxes of all species are significantly smaller at nighttime than daytime, likely due to the low turbulence (u * <0.17 m s −1 ) and significant attenuation.…”
Section: Patterns In the Fluxesmentioning
confidence: 99%
“…3 Moreover, recent evidence has also shown that sequestration of persistent organic pollutants in all snow-covered regions of the globe can have a significant influence on the overlying atmosphere. 4,5 As mentioned above, ice-halogen chemistry was first explored for its implication into the formation of the Antarctic ozone hole, a phenomenon in which the majority of ozone within the polar stratospheric vortex is depleted annually for months at a time. 1 It has thus been shown that halogens released from ice particles interacting with long-lived anthropogenic substances, such as chlorofluorocarbons (CFCs) in Polar Stratospheric Clouds (PSCs) are the principal cause for subsequent chemical reactions leading to ozone consumption.…”
Section: Introductionmentioning
confidence: 99%